2022
DOI: 10.7324/japs.2022.120921
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacological study of medicinal plants indigenous knowledge about low back pain therapy in Sumatra, Indonesia

Abstract: Indonesians have had a close relationship with traditional herbal medicine for ages to maintain their health. As a common disease in the community, low back pain (LBP) is always considered for traditional healers in their practice. However, there are still insufficient data regarding the use of medicinal plants for LBP treatment. An ethnopharmacological study was conducted in Sumatra, Indonesia, to gain information on the empirical use of medicinal plants for LBP therapy among traditional healers. The informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
(19 reference statements)
2
4
0
1
Order By: Relevance
“…According to age, our study showed that tradiherbalists in the group age from 30 -50 years and 51 -70 years were more participated in this study with percentage of 41.66% for each. Same results found by [19] in Indonesia who reported that 50.8% of participants were between age ranged > 60 years, also [18] in Morocan Rif reported that the tradiherbalists ranged age between 40 -60 years American Journal of Plant Sciences were the most participated in his study with percentage of 40.9%. These results confirm that older people are more familiar with traditional herbal medicine than other age groups, and this explain why knowledge of the properties and uses of medicinal plants is generally acquired through long experiences and passes down from one generation to the other.…”
Section: Discussionsupporting
confidence: 64%
“…According to age, our study showed that tradiherbalists in the group age from 30 -50 years and 51 -70 years were more participated in this study with percentage of 41.66% for each. Same results found by [19] in Indonesia who reported that 50.8% of participants were between age ranged > 60 years, also [18] in Morocan Rif reported that the tradiherbalists ranged age between 40 -60 years American Journal of Plant Sciences were the most participated in his study with percentage of 40.9%. These results confirm that older people are more familiar with traditional herbal medicine than other age groups, and this explain why knowledge of the properties and uses of medicinal plants is generally acquired through long experiences and passes down from one generation to the other.…”
Section: Discussionsupporting
confidence: 64%
“…Oleh karena itu sebagai langkah awal untuk mendukung peningkatan pengetahuan tentang tanama obat herbal (TOGA) terutama pada santri P2S2 Sukorejo maka perlunya pengetahuan masyarakat terutama santri P2S2 Sukorejo Kabupaten Situbondo untuk tanaman herbal apa saja yang bisa di jadikan terapi gastritis [14]. Upaya untuk membantu pencapaian peran maternal pada santri salah satunya dengan mengkonsumsi makanan yang begizi berkhasiat untuk meningkatkan pola hidup sehat yang baik dan membudidayakan tanaman herbal (TOGA) [15]. Kegiatan ini dilakukan untuk meningkatkan pengetahuan masyarakat tentang TOGA terutama pada terapi gastritis dan bisa melakukan Tindakan preventif dan kuratif dengan mandiri.…”
Section: Pendahuluanunclassified
“…Only when specialists in various fields jointly assess the patient’s condition is it possible to establish a treatment regimen tailored to each patient, which is part of the trend of personalized medicine [ 98 ]. It is also possible that, in addition to the traditionally accepted methods of treatment, the use of “unconventional” methods of treatment, such as acupuncture, herbalism, and folk medicine, should be thoroughly investigated, adding these techniques to the overall arsenal of possibilities [ 99 ]. It is also important to establish a registry of patients with LBP or LSS at the local and national, and perhaps international, levels to record and analyze the outcomes of patients at all stages of care, taking into account the various treatment methods, to better assess the effectiveness of various treatment options [ 100 ].…”
Section: Future Directionsmentioning
confidence: 99%